2000
DOI: 10.1074/jbc.275.14.10388
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Protein-disulfide Isomerase in Response to Hypoxia/Brain Ischemia and Its Protective Effect against Apoptotic Cell Death

Abstract: We isolated and identified a stress protein that is upregulated in response to hypoxia in primary-cultured glial cells. Protein-disulfide isomerase (PDI) was up-regulated not only by hypoxia in glia in vitro, but also by transient forebrain ischemia in rats in vivo. To determine whether newly synthesized PDI is involved in tolerance to ischemic stress, we carried out two procedures to induce PDI gene expression in human neuroblastoma SK-N-MC cells, as well as intrahippocampal injection following electroporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(201 citation statements)
references
References 38 publications
13
182
1
5
Order By: Relevance
“…These two sites could lead to increased PDI expression in neurons, and result in both attenuation of the loss of cell viability in vitro and reduction of the number of DNA-fragmented cells in the rat hippocampal CA1 subregion in vivo [Lyles and Gilbert, 1991]. Recent reports demonstrate that upregulated PDI may exert a protective effect against apoptotic cell death [Tanaka et al, 2000;Ko et al, 2002]. The observed downregulated expression of PDI in our study indicates that cadmium triggers neural cells towards apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…These two sites could lead to increased PDI expression in neurons, and result in both attenuation of the loss of cell viability in vitro and reduction of the number of DNA-fragmented cells in the rat hippocampal CA1 subregion in vivo [Lyles and Gilbert, 1991]. Recent reports demonstrate that upregulated PDI may exert a protective effect against apoptotic cell death [Tanaka et al, 2000;Ko et al, 2002]. The observed downregulated expression of PDI in our study indicates that cadmium triggers neural cells towards apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…82 Accumulation of immature and denatured proteins results in ER dysfunction in brains of AD, PD, ALS, prion disease, cerebral ischemia, and possibly other neurodegenerative disorders, but upregulation of PDI represents an adaptive response promoting protein refolding and may offer neuronal cell protection. [83][84][85][86][87][88][89][90] Recently, we reported that excessive NO can lead to S-nitrosylation of the active site thiol groups of PDI, and Figure 3 Possible mechanism of S-nitrosylated PDI (SNO-PDI) contributing to the accumulation of aberrant proteins and neuronal cell damage or death. ER stress is triggered when misfolded proteins accumulate within the ER lumen, inducing the UPR.…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…In the present study, we identified (with at least 3 peptides) 23 proteins with significantly increased (Table 1) and 23 proteins with decreased ( Table 2) (1) - (Chihara et al, 2007), (2) - (Folci et al, 2014), (3) - (Chen et al, 2002), (4) - (Tanaka et al, 2000), (5) - (Ding and Shen, 2008), (6) - (Na et al, 2012), (7) - (Lyon et al, 2007), (8) - (Sweatt et al, 2004), (9) - (Bahn et al, 2002), (10) - (Manya et al, 1998), (11) - (Kamada et al, 2003), (12) - (McKenna et al, 2000), (13) - (Christel et al, 2012), (GO) -According to Gene Ontology database. …”
Section: Functional Clusters Of Altered Proteinsmentioning
confidence: 99%